‘We Are Not the Same.’ Work-Related Relationships Within Roman Cities from Hispania - Arnau Lario Devesa (Frontière·s)
The Roman city was a truly complex world. A mix of cultures, social classes and religions, it was an unequal environment, with a wide range of individual or collective interactions depending on differences in rank and wealth. In a workshop, the master craftsman had journeymen and apprentices under his direct orders, and any transaction involved a paying customer and a service provider. Similarly, all workers were ultimately supervised by the municipal official and the tax collector. These factors, in conjunction with the underlying concepts of freedom (or its absence), geographic origin, age and gender, resulted in the formation of a series of socio-economic limitations (frontiers) that shaped the everyday economy-related interactions.This paper analyses the various social barriers that existed in the epigraphic record of Roman Hispania during the Early Imperial period (1st‑3rd centuries CE), with a particular focus on the interactions between clients and providers and among colleagues within the same line of work or workshop. The main objective is to ascertain the extent to which such limits, established by tradition and the legal framework, had a visible impact on the organization of the urban economy.